2008
DOI: 10.1172/jci32573e1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte GATA4 functions as a stress-responsive regulator of angiogenesis in the murine heart

Abstract: During the preparation of the manuscript, an error occurred in the wording of the final sentence of the abstract. The correct sentence appears below.To our knowledge, these results demonstrate a previously unrecognized function for GATA4 as a regulator of cardiac angiogenesis through a nonhypoxic, load, and/or disease-responsive mechanism.The JCI regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 0 publications
9
99
0
1
Order By: Relevance
“…Previous work shows that a central mechanism underpinning myocardial stress-induced angiogenesis is the release of angiogenic factors, notably VEGF (25)(26)(27). We found that cardiac VEGF-A protein levels were significantly increased in Nox4-transgenic mice whereas Nox4-null mice had markedly lower levels than wild-type after pressure overload (Fig.…”
Section: Nox4-dependent Enhancement Of Myocardial Capillary Density Dmentioning
confidence: 53%
See 3 more Smart Citations
“…Previous work shows that a central mechanism underpinning myocardial stress-induced angiogenesis is the release of angiogenic factors, notably VEGF (25)(26)(27). We found that cardiac VEGF-A protein levels were significantly increased in Nox4-transgenic mice whereas Nox4-null mice had markedly lower levels than wild-type after pressure overload (Fig.…”
Section: Nox4-dependent Enhancement Of Myocardial Capillary Density Dmentioning
confidence: 53%
“…The major mechanism underlying the beneficial effects of Nox4 during load-induced stress is an increase in myocardial capillaries, with capillary density being impaired in Nox4-null animals but better preserved in Nox4-transgenic mice compared with wild type. Myocardial angiogenesis is tightly coupled to cardiomyocyte growth during heart development (34) and is also an important determinant of the response to disease-causing stresses such as pressure overload (24)(25)(26)(27). Stress-induced angiogenesis has been shown to be underpinned by the release of VEGF from cardiomyocytes to exert paracrine effects on adjacent vessels (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Gata4 has also been shown to promote cardiac angiogenesis. For instance, conditional overexpression of GATA4 in adult cardiomyocytes increased myocardial capillary formation and increased coronary flow reserve and perfusion-dependent cardiac contractility [48]. These studies suggest that Gata4 activation in CPCs used for heart repair may have multi-faceted benefits, including promoting CPC differentiation and survival, as well as promoting cardiac angiogenesis.…”
Section: Discussionmentioning
confidence: 92%